Ubiquitous Computing Application and Wireless Sensor UCAWSN-14 - Park, James J. (Jong Hyuk).; Pan, Yi.; Chao, Han-Chieh.; Yi, Gangman; SpringerLink (Online service) (Dordrecht : Springer Netherlands : Imprint: Springer, 2015)
IT changes everyday’s life, especially in education and medicine. The goal of ITME 2014 is to further explore the theoretical and practical issues of Ubiquitous Computing Application and Wireless Sensor Network. It also aims to foster new ideas and collaboration between researchers and practitioners. The organizing committee is soliciting unpublished papers for the main conference and its special tracks.
Voronoi Diagram and Microstructure of Weldment; J. Cho, M. Choi -- High-SNR Approximate Closed-Form Formulas for the Average Error Probability of M-ary Modulation Schemes over Nakagami-q Fading Channels; H. Lee -- Performance Evaluation of IEEE 802.15.6 MAC with User Priorities for Medical Applications; L.Yang, et al -- Using Dead Reckoning, GPS and Fingerprinting for Ubiquitous Positioning; H.-H. Chiu, et al -- Multi-core Scheduling Scheme for Wireless Sensor Nodes with NVRAM-based hybrid memory; S. Oh, Y. Ryu -- Security Scheme for LTE Initial Attach; U. Jang, et al -- ASiPEC: An Application Specific Instruction-Set Processor for High Performance Entropy Coding; S.-H. Choi, et al -- An Enhanced Cooperative Spectrum Sensing Scheme based on New Rule of Combining Evidences in Cognitive Radio; M. Sajjad Khan, I.Koo -- A Design of an Intrusion-Tolerant System based on Effective Resource Conversion; S. Heo, et al -- An Adaptive Mobile Service Execution Framework in the Cloud Computing Environment; X. Yin, et al -- Trajectory Prediction for using real Data and real meteorological data; Y. Kim, et al -- The ADS-B Protection Method for Next-Generation Air Traffic Management System; S.-H. Lee, et al -- Interactive drawing Based on Hand Gesture; T.-E. Kim -- Nullifying Malicious Users for Cooperative Spectrum Sensing in Cognitive Radio Networks Using Outlier Detection Methods; P. Prasain, et al -- A Study on Electronic-Money Technology using Near Field Communication; M.-S. Jung -- A Novel Android Memory Management Policy Focused on Periodic Habits of a User; J. H. Kim, et al -- Care Record Summary Validation Tool with Social Network Service; J. W. Sin, et al -- Performance Study of an Adaptive Trickle Scheme for Wireless Sensor Networks; Y.-W. Lin, P.-H. Wang -- A New Distributed Grid Scheme utilizing Node-based Preprocessing Technique for Supporting k-NN Queries; H. Lee, et al -- A Cooperative GPS Approach for Improving Positioning Accuracy in a Location Based System; R. Islam, J. Kim -- Intelligent Evaluation Models based on Different Routing Protocols in Wireless Sensor Networks; N. Cao, et al -- Implementation of Personalized Wellness Service; M. Kim, et al -- SOM Clustering Method using user’s features to classify profitable customer for Recommender Service in u-Commerce; C. Y. Sung, et al -- A Performance Improvement Scheme for Discovery Service; P. Liu, et al -- A Cross Cloud Authorization Mechanism Using NFC and RBAC Technology; H.-S. Jan, et al -- A Study on High Security Authentication Mechanism for 3G/WLAN Networks; W.-C. Wu, H.-T. Liaw -- A Simple Authentication Scheme and Access Control Protocol for VANETs; W.-C.Wu, Y.-M. Chen -- Decision Tree Approach to Predict lung Cancer the Data Mining Technology; J.-H. Kao, et al -- Study of Customer Value and Supplier Dependence with the RFM Model; J.-H. Kao, et al -- An assistance mechanism bsed on active RFID and RSSI tracking technology for monitoring rehabilitation patients; C.-S. Wang, et al -- Feature Selection for Support Vector Machines base on Modified Artificial Fish Swarm Algorithm; K.-C. Lin, et al -- A new Remote Desktop Approach with Mobile Devices: Design and Implementation; T.-Y. Huang, et al -- Mitigating DoS Attacks based on Recovery-based ITS in Cloud; B. Jang, et al -- A Databases Strategy in Redundant Web Servers with Fault-Resilience for a Computing Grid; M.-h. Ok -- Implementation of Low Power LED Display Controller using Adiabatic Operation; K.-R. Lee, et al -- Hand Gesture Recognition using 8-Directional Vector Chains in Quantization Space; S. Lee, et al -- Forensic Artifacts in Network Surveillance Systems; K.-S. Lim et al -- Routing Protocol for Hierarchical Clustering Wireless Sensor Networks; A. Ali, et al -- The Design of a New Virtualization-based Server Cluster System Targeting for Ubiquitous IT Systems; J. Lim, et al -- A Conceptualisation of a Strategy to Optimise Shiftwork Scheduling in an Emergency Department; M. N. Azhar, et al -- The Evaluation of Pen Gestures in a Digital Painting Environment; C.-H. Ko -- Disease Pattern Analysis Using Electronic Discharge Summary of EMR in HL7 for Computerized Treatment Plan of Cancer Patients in Korea; C. Y. Sung, et al -- Research on the Network Assisted Teaching System of College Physics Experiments; Y. Du, et al -- Scheduling Model and Algorithm of Vertical Replenishment; S. Liu, B. Li -- Assisted Lung Ventilation Control System as a Human Centered Application: The Project and Its Educational Impact on the Course of Embedded Systems; D. Cabezas, et al -- Research of SSO Based on the Fingerprint Key in Cloud Computing; Z. Yongsheng, et al -- Study of Local Monitoring System Based on SMS under the Cloud Environment; Z. Yongsheng, et al -- Effects of meal size on the SDA of the taimen; G. Yang, et al -- Management Information Systems; L. Ogiela, M. Ogiela -- Security in Management of Distributed Information; M. Ogiela, et al -- Research of ABAC Mechanism Based on the Improved Encryption Algorithm under Cloud Environment; Z. Longxiang, Z. Jiashun -- A novel design of education video personalized recommendation system based on collaborative filtering recommendation technology; J. Xiao, M. Wang -- The Design of a Medical Rules Synchronization System; Y.-H. Chang, et al -- Associative Recommendation of Learning Contents Aided by Eye-tracking in a Social Media Enhanced Environment ; G. PIAO, et al -- A Novel Strategy for Colonies recognition and Classification in Super-Resolution Images; Q. Zhang, et al -- Study on Intelligent Course Scheduling System; T. Li, X. Li -- The Study and Research on Chinese Sports Network Marketing Strategy; J. Yong -- Interactive visualization of enrollment data using parallel coordinates; W. Xinglei, L. Xueqing -- The Effect of Peer’s Progress on Learning Achievement in e-Learning: A Social Facilitation Perspective; P.-S. Chiu, et al -- An Integration Framework for Clinical Decision Support Applications; Z. Xiang, et al -- Method of Generating Intelligent Group Animation by Fusing Motion Capture Data; J. Song, et al -- Histogram-Based Masking Technique for Retinal Fundus Images; R. Chong, J. Suniel -- Effect of electronic Scoring System for Scenario Group Tutorial implementation for supporting medical student studies; P. Khumrin, V. Supajatura -- Perceived Risk of Anti-Corruption e-Learning, Email Phishing Literacy, and Anomia; J. Abraham, S. Sharron -- A Model of Business Intelligence Systems for School: A Case Study (Perception Applications and Benefits); Y. Kurniawan -- A Surveillance Platform of Antimicrobial Use in Hospital Based on DDD(Defined Daily Dose); G.Liang, et al -- Identification of Adverse Drug Events in Chinese Clinical Narrative Text; C. Ge, et al -- Control system and control method for automatic adjustment of outdoor LED display brightness; F. YANG, et al -- A Novel Quantitative Evaluation Metric of 3D Mesh Segmentation; X. Sun, et al -- A Survey Analysis of Chinese Virtues Questionnaire in Medical Postgraduates; M. Yu, et al -- Practice and Exploration of All-in-English Teaching of Compiler Principles; X. Liu, H. Xu -- An Application of Ant Colony Optimization Clustering Approach for Primary Headache Diagnosis; Y. WU, H. Duan -- Analysis and Comparisons of Iterative Closest Point Algorithms; L. Wang, X. Sun -- Study on the effectiveness of distance education in the judicial examination training; R. x. Zhang, W.s. Wang -- Greedy Strategy Based Self-adaption Ant Colony Algorithm for 0/1 Knapsack Problem; D.-p. DU, Y.-r.ZU -- Non-Chinese students speak: sectional and clinical anatomy learning in a Chinese medical school ; X. He, et al -- Dynamic and Efficient Search System of Digital Encyclopedia of Intangible Cultural Heritage:The Case Study of ICHPEDIA; J. S. Lee, et al -- On the Performance of Quasi-Orthogonal Space Time Block Coded Massive MIMO with up to 16 Antennas; K. Z. Chi Winn, et al -- Encrypted data group authentication for outsourced databases; M. Jang, et al -- De-word Classification Algorithm Based on the Electric Power of Large Data Library Retrieval; X. Guo, et al.
Keywords: Electrical engineering; Computer communication systems; Coding theory; Information theory; Communications Engineering, Networks; Computer Communication Networks; Coding and Information Theory